Duration of Antimicrobial Treatment in Adult Patients with Pneumonia: A Narrative Review - Dimitra Dimopoulou; Charalampos D. Moschopoulos; Konstantina Dimopoulou; Anastasia Dimopoulou; Maria M. Berikopoulou; Ilias Andrianakis; Sotirios Tsiodras; Anastasia Kotanidou; Paraskevi C. Fragkou (MDPI AG, 2024)
Pneumonia remains a major global health concern, causing significant morbidity and mortality among adults. This narrative review assesses the optimal duration of antimicrobial treatment in adults with community-acquired pneumonia (CAP), hospital-acquired pneumonia (HAP), and ventilator-associated pneumonia (VAP). Current evidence about the impact of treatment duration on clinical outcomes demonstrates that shorter antibiotic courses are non-inferior, regarding safety and efficacy, compared to longer courses, particularly in patients with mild to moderate CAP, which is in line with the recommendations of international guidelines. Data are limited regarding the optimal antimicrobial duration in HAP patients, and it should be individually tailored to each patient, taking into account the causative pathogen and the clinical response. Shorter courses are found to be as effective as longer courses in the management of VAP, except for pneumonia caused by non-fermenting Gram-negative bacteria; however, duration should be balanced between the possibility of higher recurrence rates and the documented benefits with shorter courses. Additionally, the validation of reliable biomarkers or clinical predictors that identify patients who would benefit from shorter therapy is crucial. Insights from this review may lead to future research on personalized antimicrobial therapies in pneumonia, in order to improve patient outcomes.